Using mimicry of body movements by a virtual agent to increase synchronization behavior and rapport in individuals with schizophrenia. Issue 1 (December 2018) - Raffard, Stéphane; Salesse, Robin; Bortolon, Catherine; Bardy, Benoit; Henriques, José; Marin, Ludovic; Stricker, Didier; Capdevielle, Delphine
Abstract Synchronization of behavior such as gestures or postures is assumed to serve crucial functions in social interaction but has been poorly studied to date in schizophrenia. Using a virtual collaborative environment (VCS), we tested 1) whether synchronization of behavior, i.e., the spontaneous initiation of gestures that are congruent with those of an interaction partner, was impaired in individuals with schizophrenia compared with healthy participants; 2) whether mimicry of the patients' body movements by the virtual interaction partner was associated with increased behavioral synchronization and rapport. 19 patients and 19 matched controls interacted with a virtual agent who either mimicked their head and torso movements with a delay varying randomly between 0.5 s and 4 s or did not mimic, and rated feelings of rapport toward the virtual agent after each condition. Both groups exhibited a higher and similar synchronization behavior of the virtual agent forearm movements when they were in the Mimicry condition rather than in the No-mimicry condition. In addition, both groups felt more comfortable with a mimicking virtual agent rather than a virtual agent not mimicking them suggesting that mimicry is able to increase rapport in individuals with schizophrenia. Our results suggest that schizophrenia cannot be considered anymore as a disorder of imitation, particularly as regards behavioral synchronization processes in social interaction contexts.